PHENOMENOLOGICAL STUDY ON THE VILLAGE FUND ACCOUNTABILITY - Maritafitri, Dyah; Achadiyah, Bety Nur (Universitas Negeri Yogyakarta, 2018)
This study analyzes the accountability perception on the management of village fund in Jabon Village, Jombang district based on the executor's experience. The selected type of research is a qualitative method that paradigm the interpretive phenomenology. Based on this research, the executor manages village funds based on the incidence of failure in the village timely disburse in May 2016. They have a perception that reporting is mandatory in order for them to get the village fund. The executor does not want to experience the disappointment 2016 to reoccur. Thus, they avoid the same incident as the result of learning from experience in managing the village funds in the previous year. At each experience, there is the environment that plays a role in the process of intersubjectivity. First, through skepticism among the executor based on the stereotype that the educational background determines capability. Second, the behavior of financial managers of the village where they are always obedient to the commands of the village head, this is a repetitive action that is considered reasonable. Both forms of intersubjectivity by the work environment caused executor system to justify a different form of the duties and functions or Tugas Pokok dan Fungsi (Tupoksi). Because of this, the executor has difficulties to integrate the village fund management responsibilities to be accountable. Executor defines accountability as the responsibility of reporting vertically, while horizontal reporting is only done as a formality. The greatest thrust of executors in action is the fear of sanctions from those who are considered to have a higher position in the bureaucratic corridor. Thus, the perception of accountability, in this case, is that the necessity in the management of village funds containing different levels of urgency differs based on the focus or concern of the work environment on the management of village funds.Keywords: phenomenological